The effect of mavacamten on echocardiographic parameters, cardiac function and biomarkers in hypertrophic cardiomyopathy patients, a systematic review and meta-analysis - Zina Otmani; Noura Abdrabou; Hazem Ayman Elsayed; Mazen Negmeldin Aly Yassin; Mohamed Abouzid; Mahmoud Diaa Hindawi; Ayman K. Awad (Indian Heart Journal)
Background: Evaluate the effect of mavacamten on echocardiographic parameters and cardiac biomarkers in patients with hypertrophic cardiomyopathy (HCM). Methods: We searched PubMed, SCOPUS, Web of Science, and Cochrane Library until November 2023. Results were reported as mean difference (MD) and Risk Ratio (RR) with 95 % confidence intervals (CI). Results: Seven studies with 524 patients (456 with obstructive HCM and 59 with non-obstructive HCM) were included. Mavacamten significantly improved septal early diastolic mitral annular velocity (e') (MD 0.78, 95 % CI [0.51 to 1.05]) and left ventricular mass index (LVMI). It reduced left ventricular outflow tract (LVOT) gradient, NT-proBNP (MD -557.14, 95 % CI [-685.59 to −428.68]), and troponin levels. Improvements were also seen in left atrial volume index (MD -6.26, 95 % CI [-8.88 to −3.63]) and E/e' ratios, particularly in obstructive HCM patients. Conclusion: Mavacamten enhances echocardiographic and cardiac biomarker outcomes in HCM patients on short-term follow-up. Limited data on non-obstructive HCM require cautious interpretation.